Formation of Financial Mechanisms Corporate Sustainable Development: Methods of Risk Assessment - Рогов, Г. К. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2015)
Creating a system of financial mechanisms of corporate sustainability means radical changes in business environment. As a result of this process organizations (especially those with low corporate environmental and social standards) will face a range of adaptation risks that may affect the achievement of their objectives. These risks have specific features. The article deals with comparative analysis of systematic techniques for risk assessment included in ІЕС 31010: 2009 standard (Risk management – Risk assessment techniques). The optimal techniques for assessing the risks connected with the development of corporate sustainability financial mechanisms are defined on the basis of this analysis (FTA, ETA, Cause-consequence analysis, Cause and effect analysis, Bow tie analysis, Consequence / probability matrix). The techniques that can be used only for risk identification or assessing inefficiency of adaptation measures are also identified. Reliable assessment of the risks related to the formation of corporate sustainability financial mechanisms and ineffectiveness of adaptation process, on the basis of defined techniques, must be an integral part of corporate sustainability management. The purpose of further research is to specify risk assessment methodology in the process of reforming the tax and budgetary systems and the gradual formation of investment, credit and insurance mechanisms of corporate sustainable development.